Introduction (Reporting) to Employers and Ordinary Workers and the Need for Compulsory Insurance Against Accidents as a Method of Qualified Management, Ensuring Safety and Labor Protection, and Improving the Welfare of Workers, Business Entities and the S - A., Rayimkulov; Mikhailovich, Badadyan Sergey (European Journal of Life Safety and Stability (2660-9630), 2022)
The article deals with issues related to the need to introduce into practice a mandatory accident insurance policy, which is issued by the employer by its legal entity, which is a socio-economic and one of the legal guarantors of the rights and obligations of the employer and employee when concluding an official employment contract.